O documento curricular integrado do arranjo de desenvolvimento educacional dos Guarás: o que é possível dizer sobre o ensino de Ciências com base em temas regionais - SANTANA, Verônica Maria De Moraes Alexandre (2023)
The educational process has sought to follow the transformations and evolutions inherent to current times, especially with regard to advances in the way of teaching and learning science. To offer Science teaching consistent with students’ experiences, it is necessary to think about the possibility of redefining the teaching and learning process and its planning in the classroom. This study is guided by the following questions: how is the implementation of the Integrated Curricular Document (DCI) of the Guarás Educational Development Arrangement (ADE) present in the physical infrastructure, in the Political-Pedagogical Projects (PPPs) of schools and in the articulation of pedagogical activities? What is the teaching vision regarding Science teaching following the implementation of the DCI of the ADE dos Guarás? Based on these guiding questions, the general objective of the research was outlined: Understanding the different perceptions of the implementation of the DCI of the ADE dos Guarás in the initial years of schools in the city of Bacuri/MA. The study is of an exploratory qualitative nature, combined with explanatory and documentary nature. The research subjects are, in the first stage, the municipal education directors of the municipalities of ADE dos Guarás and, in the second stage, the teachers who teach the Science subject in the initial years of Elementary Education, in two schools in the municipal education network, in the municipality of Bacuri/MA. The instruments used to produce the data were questionnaires, semi-structured interviews and the schools’ PPPs. The PPPs of the schools in question, the results of the questionnaires applied to management and the transcripts of the semi-structured interviews conducted with science teachers at these institutions made up the corpus of the research. The data was analyzed and interpreted using Discursive Textual Analysis (ATD), as idealized by Moraes and Galiazzi (2016). As a result, it was found that these PPPs include actions in line with the DCI of the ADE dos Guarás, with regard to contextualized and problematized teaching based on regional themes. The perception of the science teachers pointed to a possible re-signification of science teaching as a result of the implementation of this document. In addition, there was a need to improve the physical infrastructure of schools in order for it to be effectively implemented.